Learning Mother Learning Model Model In Early Age 4 - 6 Years - Dwingki Marta Putra; Megi Personi; Dodi Ertanto (Sinar Sport Journal, 2022)
The purpose of this research and development is to produce a basic motion learning model jump for early childhood. In addition, this research and development is conducted to obtain information in depth about the development and implementation of learning model of basic jumping motion and to know the effectiveness, efficiency and attractiveness of the child on the model made. The instruments used in this research and development are questionnaires, questionnaires, and basic jump motion test instruments used to collect baseline jump data. The stages of research and development are: (1) needs analysis, (2) expert evaluation (initial product evaluation), (3) limited trials (small group trial), and (4) field testing. Model effectiveness test using motion correctness test, from the initial test conducted obtained the level of basic motion capability jumped 2074, then after given the treatment obtained for 2284. So the basic motion learning model jumps for early childhood is declared effective in improving learning basic motion jump on early childhood. Based on the results of the development it can be concluded that: (1) With the basic motion learning model jumping learners can learn effectively and efficiently, (2) With the learning model of jumping ground motion that has been developed, obtained evidence of improvement, testing data of pretest and posttest result of significant difference between before and after existence of treatment on model.